The impact of internet use on old-age support patterns of middle-aged and older adults - Wang, Jingyi; Gao, Lifei; Wang, Guojun; Hu, Baibao (Frontiers in Public Health, 2023)
The trend towards low fertility and low mortality is prominant worldwide. The accelerating ageing and the pressure on public pensions are making the ‘dependent pattern of old-age support’, which relies on family and government, unsustainable. It is urgent for people to change their mindset about ageing and to develop a sense of ‘relying on themselves for old-age support’. This study incorporates the commercial pension insurance, formal care and the attitude towards independent old-age support pattern into the framework of ‘independent pattern of old-age support’, where the commercial pension insurance and formal care indicates financially and mentally independent patterns of old-age support. This study examines the impact of internet use on old-age support patterns of middle-aged and older people based on the CGSS 2012-2018 five-period data. We find that the more frequent internet use increased the likelihood of purchasing commercial pension insurance, accepting formal care, and endorsing independence in later life. The channel analysis finds that the internet can promote the acceptance of independent pattern of old-age support by delivering information and facilitating social interaction. This finding provides important empirical and theoretical references for ageing countries to further transform old-age support patterns.